The Ethics of Knowledge Organization and Representation from a Bakhtinian Perspective - Arboit, Aline Elis [UNESP]; Guimaraes, Jose Augusto Chaves [UNESP] (Ergon-verlag, 2015)
This paper arises from the possibility of a theoretical dialogue between the socio-cognitive perspectives of knowledge organization and the Bakhtinian concepts on conscience, responsible act, responsive understanding, and polyphony as attitudes that motivate the dialogism that is inherent to language. Those questions allow us to recognize the professional that organizes and represents knowledge as someone who has an intersubjective conscience, a product composed by two axes that are indeed deeply connected: the self and the other. Therefore, the acts of representing and organizing knowledge are deeply affected by external discourses and by internal discourses. Those different discourses come together at the moment of representing the knowledge and act as a response to the dialogues between the external and the internal discourses. As a consequence, the indexing/classification codes, terms or signs assume a dialogical and dynamic representativeness in order to correspond not only to the contents of the documents but also to dialogue with a diverse user community, by the recognition of the alterity/otherness of the social actors and the social situations. Finally, it is important to point out the need of an ethical and democratic attitude of the indexer/classifier, in order to represent the social pluralism and show an equipollence of social voices.
Keywords: ethics; knowledge organization; knowledge representation; Bakhtin; subject; language; social voices; consciousness